ACT OF REPRESENTATIVE WITHIN OBAMA’S SPEECH AT INTERFAITH PRAYER VIGIL IN NEWTOWN, CONNECTICUT - WIBOWO, YOEL (Jurnal Ilmiah Mahasiswa FIB, 2013)
One particular tool commonly used by people in delivering thoughts  is  speech,  in  this  case,  formal  speech.  Collecting Illocutionary Actions within formal speech is very interesting activity.  By analyzing Illocutionary Actions, people can reveal the intended meaning of the speaker. The data source in thisresearch is  taken from  the script  of  Obama‟s  formal  speechdelivered at Interfaith Prayer Vigil in Newtown, Connecticut.The objectives of this research are to propose a list of Act ofRepresentative and to provide an analysis about Act of Representative inside the speech, by connecting the Act of Representative found with the prevailing circumstances in USA when the speech were delivered.    By collecting some of the representative acts in the Obama‟s speech,  the writer is able to provide some thorough analysis toward some truths and factsspoken by  Obama himself, as the president of the United States of America.        There are 22 representative acts in the Obama‟s Speech delivered at Interfaith Prayer Vigil in Newtown, Connecticut.   The truths and facts themselves talk about some different themes, such us religious themes, family, future US policy, shootings tragedy, and the circumstances in the relatedneighborhood. Key words: Act of Representative, Obama, Obama‟s Speech at Interfaith Prayer Vigil in Newtown, Connecticut